Topological entropy of diagonal maps on inverse limit spaces - Anušić, Ana; Mouron, Christopher (Topological Methods in Nonlinear Analysis, 2022)
We give an upper bound for the topological entropy of maps on inverse limit spaces in terms of their set-valued components. In a special case of a diagonal map on the inverse limit space $\underleftarrow{\lim}(I,f)$, where every diagonal component is the same map $g\colon I→ I$ which strongly commutes with $f$ (i.e.\ $f^{-1}° g=g° f^{-1}$), we show that the entropy equals $\max\{\mbox{\rm Ent}(f),\mbox{\rm Ent}(g)\}$. As a side product, we develop some techniques for computing topological entropy of set-valued maps.